Peran Kepala Madrasah dalam Meningkatkan Kompetensi Guru di MIN 3 Kota Lhokseumawe - Ramlan, Ramlan (Medan Resource Center, 2023)
This research discusses the role of madrasa heads in improving teacher competency. Professional competence is the ability to master broad and in-depth learning material that enables guiding students to meet the competency standards set out in National Education Standards. A professional teacher is not only competent in the mastery of the material, the use of appropriate methods, but there is also a desire to always improve the professional abilities and the desire to always develop strategies in carrying out their duties as instructors as well as educators so that the teaching-learning process can reach the level optimal. The head of the madrasah approaches the teachers and then makes plans in the form of seminars, training, seminars, workshops, MGMP activities. The implementation carried out by the madrasa head involves involving teachers in activities such as workshops, upgrading, MGMP and seminars.